The anti-Toxoplasma activity of the plant natural phenolic compound piceatannol - Jiang, Yucong; Shi, Yuehong; Hu, Dandan; Song, Xingju (Frontiers in Veterinary Science, 2022)
Toxoplasma gondii is an obligate intracellular protozoan that infects the nucleated cells of warm-blooded animals and causes life-threatening disease in immunocompromised patients. Due to the limited effectiveness and prominent side effects of existing drugs, there is an urgent need to develop new therapeutic options against T. gondii. Piceatannol is a natural plant compound with multiple functions such as antibacterial, antileukemic and antiparasitic activities. In the present study, the anti-T. gondii activity of piceatannol was evaluated. Piceatannol potently inhibited Toxoplasma with a half-maximal effective concentration (EC50) of 28.10 μM. Piceatannol showed a significant inhibitory effect on intracellular proliferation, inhibiting intracellular parasites at a rate of 98.9% when treatment with 100 μM piceatannol. However, the invasion ability of tachyzoites was not affected by piceatannol. By immunofluorescence assay, we noted that the parasite showed abnormalities in cell division after exposure to piceatannol. To determine the in vivo effect of piceatannol on acute infection, a model was established by infecting BALB/c mice with the virulent RH strain of T. gondii. Mice infected with 500 tachyzoites showed a significant therapeutic effect when treated with 15 mg/kg of piceatannol. These results suggest that piceatannol is a promising drug for the treatment of T. gondii.